Influence of a 100-mile ultramarathon on heart rate and heart rate variability. Issue 2 (13th May 2021) - Paech, Christian; Schrieber, Simone; Daehnert, Ingo; Schmidt-Hellinger, Paul Jürgen; Wolfarth, Bernd; Wuestenfeld, Jan; Thouet, Thomas
Abstract : Aims: This study aimed to investigate the impact of an ultramarathon (UM) with a distance of 100 miles on heart rate (HR) and heart rate variability (HRV). Methods: 28 runners (25 men and 3 women) underwent 24-hour Holter ECG monitoring 1 week before the UM, immediately after the UM and after a week of recovery. The influence of age, body mass index (BMI), HR and HRV on the run time and recovery was investigated. Results: A rise in the baseline HR (18.98%) immediately after the run accompanied by a significant drop in the SD of all normal RR intervals (7.12%) 1 week after. Except for the runners' age, BMI, HR and HRV showed no influence on the competition time. Full return of HRV to the athletes' baseline did not occur within 1 week. There were no significant differences between finishers and non-finishers in the analysed parameters. Conclusion: The present results show that a 100-mile run leads to an increase in sympathetic activity and thus to an increase in HR and a decrease in HRV. Also, HRV might be a suitable parameter to evaluate the state of recovery after a 100-mile run but does not help to quantify the status of recovery, as the damage to the tendomuscular system primarily characterises this after completing a UM.